Respiratory Heterogeneity Shapes Biofilm Formation and Host Colonization in Uropathogenic Escherichia coli - Connor J. Beebout (American Society for Microbiology, 2019)
ABSTRACT Biofilms are multicellular bacterial communities encased in a self-secreted extracellular matrix comprised of polysaccharides, proteinaceous fibers, and DNA. Organization of these components lends spatial organization to the biofilm community such that biofilm residents can benefit from the production of common goods while being protected from exogenous insults. Spatial organization is driven by the presence of chemical gradients, such as oxygen. Here we show that two quinol oxidases found in Escherichia coli and other bacteria organize along the biofilm oxygen gradient and that this spatially coordinated expression controls architectural integrity. Cytochrome bd, a high-affinity quinol oxidase required for aerobic respiration under hypoxic conditions, is the most abundantly expressed respiratory complex in the biofilm community. Depletion of the cytochrome bd-expressing subpopulation compromises biofilm complexity by reducing the abundance of secreted extracellular matrix as well as increasing cellular sensitivity to exogenous stresses. Interrogation of the distribution of quinol oxidases in the planktonic state revealed that ∼15% of the population expresses cytochrome bd at atmospheric oxygen concentration, and this population dominates during acute urinary tract infection. These data point toward a bet-hedging mechanism in which heterogeneous expression of respiratory complexes ensures respiratory plasticity of E. coli across diverse host niches. IMPORTANCE Biofilms are multicellular bacterial communities encased in a self-secreted extracellular matrix comprised of polysaccharides, proteinaceous fibers, and DNA. Organization of these components lends spatial organization in the biofilm community. Here we demonstrate that oxygen gradients in uropathogenic Escherichia coli (UPEC) biofilms lead to spatially distinct expression programs for quinol oxidases—components of the terminal electron transport chain. Our studies reveal that the cytochrome bd-expressing subpopulation is critical for biofilm development and matrix production. In addition, we show that quinol oxidases are heterogeneously expressed in planktonic populations and that this respiratory heterogeneity provides a fitness advantage during infection. These studies define the contributions of quinol oxidases to biofilm physiology and suggest the presence of respiratory bet-hedging behavior in UPEC.